2006
DOI: 10.1149/1.2160432
|View full text |Cite
|
Sign up to set email alerts
|

Germanium Incorporation in HfO[sub 2] Dielectric on Germanium Substrate

Abstract: It is widely reported that a significant amount of germanium is incorporated in HfO 2 gate dielectric during the formation of highgate stack on germanium substrate. In this paper, the dependences of germanium incorporation in HfO 2 on dielectric deposition method, annealing temperature, and annealing ambient were extensively studied by physical methods such as time-of-flight secondary ion mass spectroscopy. The results indicate that the high thermal budget of processes, including deposition and annealing, is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Sequentially, poor interface properties and high gate leakage current will be exhibited in the Ge-MOS device. [3][4][5][6][7] Various pre-gate surface modification techniques, such as surface nitridation or Si passivation, have been developed to improve the quality of gate insulator/Ge interface. 13 It was also reported that high-performance Ge MOSFET could be realized by careful control of interfacial GeO 2 formation.…”
mentioning
confidence: 99%
“…Sequentially, poor interface properties and high gate leakage current will be exhibited in the Ge-MOS device. [3][4][5][6][7] Various pre-gate surface modification techniques, such as surface nitridation or Si passivation, have been developed to improve the quality of gate insulator/Ge interface. 13 It was also reported that high-performance Ge MOSFET could be realized by careful control of interfacial GeO 2 formation.…”
mentioning
confidence: 99%
“…Previous studies [15] on HfO 2 deposited on Ge substrates indicate Ge in-diffusion and incorporation into the oxide upon thermal treatment in N 2 at temperature T a > 600 ˚C. Therefore, we analyzed the electron trap distribution in samples annealed at 500, 700 or 1000 ˚C in N 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A thermallyevaporated HfO 2 layer, which was deposited directly on Ge substrates, showed low leakage current characteristics and poor interface quality with low accumulation capacitance values upon N 2 annealing. 10) Wu et al 11) and Zhang et al 12) observed severe Ge incorporation into HfO 2 occurring during thermal annealing due to a haphazard IL between the HfO 2 and Ge. Chen et al 13) described degraded electrical properties on Ge substrates with different high-k gate dielectrics such as HfO 2 and Al 2 O 3 without an intentional IL after annealing in a forming gas (FG) ambient at $500 C, due to direct contact between the high-k material and the Ge.…”
Section: )mentioning
confidence: 99%